3D–printing of materials with anisotropic heat distribution using conductive polylactic acid composites. (15th July 2017) - Zhuang, Yuan; Song, Wentong; Ning, Gang; Sun, Xueyan; Sun, Zhongzheng; Xu, Guowei; Zhang, Bo; Chen, Yening; Tao, Shengyang
Abstract: A series of plastic items with anisotropic heat and resistance distribution were prepared by 3D printing. Conductive graphene doped polylactic acid (G-PLA) and pure PLA were used as raw materials. The programmed mixing printing method was adopted to construct these objects. The effects of the extrusion ratios of G-PLA and PLA, applied voltage and heat distribution on the printed items were investigated. We observed that the resistance of the printed items was controlled by the extrusion ratio during the 3D printing process. The distribution of the resistance is programmed by the slicing software and the single chip microcomputer in the 3D printer. The temperature of the printed test sheet varied from 20 to 90 °C according to the applied electronic current and voltage. Heterogeneous temperature regions were identified and showed isotropy. The temperature gradient field was constructed by designing and printing items with a quasi-continuously change resistance. The thermal signal was presented in the form of color information through a thermography device. As such, a simple message can be expressed and stored in this printed objects. Graphical abstract: Highlights: Graphene doped polylactic acid (G-PLA) and PLA were used to construct anisotropic materials by a desktop 3D printer. The resistance distribution of the printed sheet can be controlled by printing program and microcomputer of a 3D printer. The heterogeneous anisotropic temperature field easily formed on printed objects when a low voltage was applied.